2009
DOI: 10.4049/jimmunol.0901310
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Turkey MHC: Sequence and Genes of the B Locus

Abstract: The MHC, the most polymorphic and gene dense region in the vertebrate genome, contains many loci essential to immunity. In mammals, this region spans ∼4 Mb. Studies of avian species have found the MHC to be greatly reduced in size and gene content with an overall locus organization differing from that of mammals. The chicken MHC has been mapped to two distinct regions (MHC-B and -Y) of a single chromosome. MHC-B haplotypes possess tightly linked genes encoding the classical MHC molecules and few other disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 59 publications
(61 reference statements)
3
54
0
1
Order By: Relevance
“…BLAST search approaches in chicken, turkey, quail, black grouse, and zebra finch failed to detect genes for immuno-and thymoproteasome, suggesting that they have been lost in the lineage of birds (Balakrishnan et al 2010;Chaves et al 2009;Shiina et al 2007;Shiina et al 2004;Sutoh et al 2012;Wang et al 2012). While the genes coding for the catalytic subunits β1i and β5i are present in the class II region of the human and murine MHC loci, sequence searches in chicken genome databases revealed that there are no LMP genes in the avian MHC region, and also the immune subunit β2i could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…BLAST search approaches in chicken, turkey, quail, black grouse, and zebra finch failed to detect genes for immuno-and thymoproteasome, suggesting that they have been lost in the lineage of birds (Balakrishnan et al 2010;Chaves et al 2009;Shiina et al 2007;Shiina et al 2004;Sutoh et al 2012;Wang et al 2012). While the genes coding for the catalytic subunits β1i and β5i are present in the class II region of the human and murine MHC loci, sequence searches in chicken genome databases revealed that there are no LMP genes in the avian MHC region, and also the immune subunit β2i could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of the turkey B-locus (Chaves et al, 2009b) established the presence of three classical class IIB loci with at least two loci being expressed in the spleen. Goto et al (2002) described the use of single-strand conformation polymorphism for assaying MHC polymorphism in the chicken.…”
Section: Mhc Genotypingmentioning
confidence: 99%
“…For consistency, the same PCR products used for DGGE were cloned using a pDrive Cloning Kit (Qiagen), transformed into DH5a cells (Invitrogen, Carlsbad, CA, USA), and over 20 purified plasmids were sequenced per individual. In addition, locus-specific primers (Chaves et al, 2009b) were used to individually sequence portions of the three known MHC-B class IIB genes from the single wild bird collected from Minnesota. Sequences of exon 2 were translated to identify putative PBR alleles.…”
Section: Ld Chaves Et Almentioning
confidence: 99%
See 2 more Smart Citations